Diversité et état de conservation de la flore ligneuse des îlots forestiers du massif montagneux de Lubero (R.D. Congo) - Norbert Kambale Ndavaro; Walere Muhindo Sahani; Armand Kuyéma Natta; Apollon D.M.T. Hegbe; Ramdan Dramani; Aliou Dicko (VertigO)
Knowledge of floristic diversity's classical measures is crucial to support conservation strategies of plant resources in degraded forests. The present study aims firstly to assess the parameters of specific and structural diversity of the woody flora of the forest patches of Lubero and secondly, to determine its state of conservation in order to suggest appropriate measures for its sustainable management. A stratified cluster sampling has been used for the forest inventories. To this end, 297 plots of 50 m2 each have been marked out in ten forest patches. Specific diversity indices have been calculated and dendrometric parameters have been determined. Renyi entropy has been calculated to compare the alpha diversity of woody species between the different forest patches. The Kruskal-Wallis rank test and analysis of variance have been used to compare structural diversity parameters between woody stands. A total of 104 woody species (86 genera and 45 families) have been identified. The species richness of the forest patches nowadays varies between 11 and 78. The Shannon diversity index is highly variable (1.98 to 4.03 bits) and the Pielou equitability is fairly high (0.83 to 0.94). Highly significant differences in density (degree of freedom ddl=9, chi-square = 93.1316, P